2019
DOI: 10.3389/fmicb.2019.01075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantamatrix Multiplexed Assay Platform and GenoType MTBDR Assay Using Smear-Positive Sputum Specimens From Patients With Multidrug- Resistant/Extensively Drug-Resistant Tuberculosis in South Korea

Abstract: Rapid detection of drug-resistant tuberculosis (DR-TB) is crucial for timely treatment and management. The GenoType MTBDR plus and MTBDR sl (MTBDR) assays have been endorsed by the World Health Organization (WHO) for the detection of DR-TB. However, MTBDR assays cannot simultaneously detect multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB). Furthermore, interpretation of the MTBDR assay requires trained people, and the assay has low sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The traditional phenotypic DSTs lead serious delays to the detection of resistance just because of the extremely slow growth of M. tuberculosis . However, several commercial diagnostic tests such as GeneXpert MTB/RIF, Genotype MTBDRplus/MTBDRsl assays, have been developed to rapidly detect both first- and second-line drug resistance in M. tuberculosis by scanning the associated mutations (Xie et al, 2017; Kim et al, 2019). Our performance showed that analysis of the associated mutations was recommended to provide a good sensitivity for rapid verification of FQ r (79.4%), SLID r (50.8%), Pre-XDR (80.4%), and XDR (92.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The traditional phenotypic DSTs lead serious delays to the detection of resistance just because of the extremely slow growth of M. tuberculosis . However, several commercial diagnostic tests such as GeneXpert MTB/RIF, Genotype MTBDRplus/MTBDRsl assays, have been developed to rapidly detect both first- and second-line drug resistance in M. tuberculosis by scanning the associated mutations (Xie et al, 2017; Kim et al, 2019). Our performance showed that analysis of the associated mutations was recommended to provide a good sensitivity for rapid verification of FQ r (79.4%), SLID r (50.8%), Pre-XDR (80.4%), and XDR (92.9%).…”
Section: Discussionmentioning
confidence: 99%
“…As the LPA kits were received at a subsidized cost, we are unable to perform a cost comparison among the molecular diagnostics in an ideal scenario. However, a recent study from South Korea analyzed the costs associated with various methodologies for DST ( Kim et al, 2019 ). A similar analysis of associated costs in India may inform policies related to the appropriate application of these methodologies for the detection of drug-resistance in clinical, programmatic and research settings.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, rapid molecular detection methods have become an important need in the definition of resistance 20 . Since the commercial molecular tests (Xpert MTB / RIF, GenoType MTBDR / MTB DRplus, sequence analysis) used for this purpose are expensive and require infrastructure, studies are continuing on fast, practical and inexpensive tests to identify resistance 21,22 .…”
Section: Discussionmentioning
confidence: 99%